2019
DOI: 10.5507/euj.2018.009
|View full text |Cite
|
Sign up to set email alerts
|

Video modeling and Test of Gross Motor Development-3 performance among children with autism spectrum disorder

Abstract: The purpose of this study was to explore the effects of video modeling on Test of Gross Motor Development-3 (TGMD-3) performance among children with autism spectrum disorder (ASD). Thirteen participants with ASD were assessed under two separate TGMD-3 protocol conditions-traditional and video modeling. Raters were blind to the protocol condition they were observing in order to prevent bias towards one condition. Total gross motor scores were analyzed using a one-way repeated-measures ANOVA. While improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
1
10
0
3
Order By: Relevance
“…The recruitment and retention rate recorded in this study were within the range of recruitment rates found previously with children with ASD [ 29 , 30 ]. Families of children with ASD often have multiple obligations related to their children’s care, which conflict with making physical activity a priority [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The recruitment and retention rate recorded in this study were within the range of recruitment rates found previously with children with ASD [ 29 , 30 ]. Families of children with ASD often have multiple obligations related to their children’s care, which conflict with making physical activity a priority [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…Interviews throughout the intervention lasted The TGMD-3 comprises six locomotor skills and seven ball skills that are developmentally appropriate for ages 3 to 10 [28]. However, this assessment has also been used with children with ASD ages 10 to 16 [29]. Locomotor skills include the run, horizontal jump, gallop, slide, skip, and hop.…”
Section: Acceptabilitymentioning
confidence: 99%
“…Em relação à classificação por sexo, apenas três artigos incluíram somente meninas (Rosa Neto et al, 2013;Ament et al, 2015;Choi et al, 2018), treze artigos incluíram somente meninos (Casey et al, 2015;Teixeira-Machado, 2015;Goff et al, 2016;Colebourn et al, 2017;Pan et al, 2017;Pereira et al, 2017;Case et al, 2018;Oliveira et al, 2018;Diniz et al, 2019;Santos et al, 2018;Vukićević et al, 2019;Fernandes et al, 2020;Oliveira et al, 2020), enquanto que os demais estudos (n=45) avaliaram ambos os sexos. Em relação aos sexos, 73,7% dos estudos conteve em suas amostras sujeitos de ambos os sexos, 21,3% sujeitos apenas do sexo masculino e 4,9% apenas sujeitos do sexo feminino.…”
Section: Sexounclassified
“…Doze estudos avaliaram especificamente habilidades motoras fundamentais em crianças com TEA, e destes estudos quatro fizeram diagnóstico do desempenho motor dos sujeitos estudados (MacDonald et al, 2013;Liu et al, 2014;Mache & Todd, 2016;Krüger et al, 2019) enquanto que oito verificaram os efeitos de programas de intervenção nessas habilidades motoras (Allen et al, 2017;Breslin & Rudisill, 2011;Case et al, 2018;Edwards et al, 2016;Felzer-Kim et al, 2020;Goff et al, 2016;Henderson et al, 2016;Krüger et al, 2018). Nos quatro estudos diagnóstico que avaliaram habilidades motoras de locomoção e de controle de objetos, foi encontrado desempenho inferior em relação aos pares sem o TEA (Liu et al, 2014;MacDonald et al, 2013;Mache et al, 2016;Krüger et al, 2019).…”
Section: Estudos Que Avaliaram Habilidades Motorasunclassified
See 1 more Smart Citation